Geodiversity Assessment as a First Step in Designating Areas of Geotourism Potential. Case Study: Western Carpathians - Chrobak, Anna; Novotný, Ján; Struś, Paweł (Frontiers in Earth Science, 2021)
Geodiversity is the natural diversity of features of geological structure, relief, and soil cover, including the relationships between these features, their properties, and their impact on other elements of the natural and cultural environment. It is described and analyzed using various types of quantitative, qualitative, or quantitative–qualitative methods. The concept of a geodiversity map presented in this article belongs to the third of these groups of methods. Despite the use of optimization methods in the form of a hexagon grid or the analytic hierarchy process calculator, it still remains partially subjective. The use of this method to calculate the geodiversity of an entire province (the Western Carpathians) gives a general view of the natural diversity of this area and allows regions to be selected for more detailed analyses or comparisons to be made between them. The geodiversity map is also a very good background on which to illustrate geotourist potential, which is expressed in terms of the number and distribution of geosites. However, in the case of the Western Carpathians, these two variables do not correlate with each other.